Cognitive perspective of metaphors in Chinese Hua'er folksongs - Zhang, Xiaojin (Frontiers in Communication, 2024)
The cognitive frame and transferences from sources to targets of metaphor study has been evident in humanities. The present article aims at the comparison in Chinese heritage Hua'er folksongs, Chinese new poetry, Chinese prose, Chinese news reportage and Chinese news editorials. By adopting the indicator I1, the results yield that A=B metaphor is typical representative of Chinese Hua'er folksongs. At a more detailed level of comparison of the a-index, heritage folksong Hua'er bears the lowest level of metaphoricity for its repeated use of the metaphorical lexis both in the target domain and source domain. The genre-specific metaphorical expressions in Chinese poetic texts show that the higher a-index is, the more metaphoricity and more cognitive effort will be. The nominalized metaphorical expressions in heritage Hua'er might limit the working memory constraints and the cognitive mastery of source-to-target structure for the singers to create metaphors.